Providing Comprehensive Medication Management in Telehealth. Issue 2 (16th January 2018) - Badowski, Melissa E.; Walker, Scot; Bacchus, Shaffeeulah; Bartlett, Sandy; Chan, Juliana; Cochran, Kelly A.; Coon, Scott; Liedtke, Michelle; Phillips, Bradley G.; White, Taylor
Abstract : The goal of this white paper is to provide direction for clinical pharmacists providing telehealth. Telehealth care is rapidly emerging to improve patient access to health care and optimize patient health outcomes. With the increasing ability to access electronic health record portals, as many as 75 million telehealth encounters are expected in North America annually. Although electronic "point of access" undoubtedly increases the use of medical and pharmacy services, the real value of telehealth lies in improved access to patients in remote areas lacking adequate medical and pharmacy services and to high‐risk patients requiring frequent monitoring. This document is intended to serve as a guide for those interested in or already using telehealth to provide direct patient care. Specifically, it focuses on general concepts of telehealth and demonstrates how the delivery of comprehensive medication management (CMM) by telehealth aligns with the Standards of Practice for Clinical Pharmacists set forth by the American College of Clinical Pharmacy. Although clinical pharmacists must be appropriately credentialed and privileged to provide CMM, their process of care must also be adapted to suit the remote patient. Patient assessment, evaluation of medication therapy, development and implementation of a plan of care, follow‐up, monitoring, and documentation of all processes of care are influenced by the technology available, the collaborations established, and the applicable regulations and requirements for telehealth practice.